Theoretical fundamentals of development of agricultural tourism in modern conditions - Tyapukhin, A.P.; Tasmaganbetov, A.B.; Кultanova, А.Е. (BUKETOV BUSINESS REVIEW, 2019)
The article deals with the development of agricultural tourism contributing to the reduction of social tension in rural areas by creating new alternative jobs and the development of rural areas. The author of the article defines the subjects of agricultural tourism: rural residents, owners of subsidiary farms and farms. The development of agricultural tourism provides financial resources to the subjects, increasing the income of their families, rural residents, and local budget revenues. In the article, along with the natural and ecological and cultural and historical resources of rural areas, the main attention is paid to the housing stock adapted for the reception of tourists: accommodation on farms in the same dwelling with the owner, rent of the whole house, accommodation in historical buildings in the countryside, separate accommodation in a rural hotel and others. According to the authors, depending on the purpose of recreation, agricultural tourism can be differentiated into the following types: health tourism; traditional tourism; educational tourism; agricultural tourism; culinary tourism; combined tourism. The article identifies the main causes and directions of development of agricultural tourism, which contributes to the development of small business; improvement of infrastructure; education of new workers; contributes to the economic stabilization and improvement of rural infrastructure; preservation of national cuisine and historical and cultural heritage.